Alternative Improving the Quality of Sub-Voltage Transmission System using Static Var Compensator. (March 2017) - Hasbullah,; Mulyadi, Y
Abstract: This study discusses the voltage profile improvement method in the transmission sub-systems using one of the devices from Flexible Alternating Current Transmission Systems (FACTS), by using a Static Var Compensator (SVC) with the object focused on electric power system sub-systems in South Bandung area and Ujung Berung. The aims of the study were to determine the voltage profile sub-systems in South Bandung and Ujung Berung before and after installation of SVC and also to determine the position and capacity of SVC in maintaining optimal voltage profile transmission sub-system. The research method used the power flow simulation from Newton-Raphson method with ETAP 7.0. The flow of reactive power had been set so that the power loss on the network (losses) system obtained a minimum. The results of the simulation and power flow analysis shows that the average voltage profile and quality of installation SVC voltage sub-systems after the optimal position and capacity to be better compared to prior to installation. By minimizing the power loss on the network, the bus voltage profile can be maintained in the values that are allowed, so the quality and continuity of operation in the power system can be maintained.